Enterprise Group Restructuring: Dutch Options and United States Enforcement - Warner, G. Ray; Veder, Michael (European Insolvency and Restructuring Journal, 2021)
On 1 January 2021 the Dutch Wet Homologatie Onderhands Akoord, also referred to as the Dutch scheme, entered into force. The Dutch scheme represents a robust restructuring framework that incorporates many of the main restructuring concepts from both the English scheme of arrangement and US chapter 11. It also adds a few new restructuring tools that will make it easier to restructure enterprise group debt by expressly providing that a restructuring plan may include the release of group guarantees and by adopting liberal jurisdictional rules that should permit proceedings to be opened in the Netherlands for all members of an enterprise group. This paper analyses the recognition and enforcement in the United States of restructuring plans adopted and confirmed in the Netherlands under the new Dutch scheme legislation, with a particular focus on the release of group guarantees. Our conclusion is that the US chapter 15 recognition and enforcement rules are very liberal and should provide little difficulty in obtaining recognition and enforcement of group restructuring plans. The very flexible US rules on COMI may result in the US courts treating the Netherlands as the COMI of all group members, thereby making the proceedings involving the non-Dutch group members foreign main proceedings. But even absent a Netherlands COMI, a Dutch scheme and its affiliate release provisions could be enforced for the benefit of all group members in a chapter 15 proceeding.